Mycobacterium marinum epididymoorchitis: case report and literature review - Macek, P; Bodnarova, M; Zavada, J; Jezek, P; Pavlik, I; Slany, M; Havelkova, M; Stork, J; Duskova, J; Hanus, T; Kocvara, R (Urologia internationalis, 2011)
Mycobacterium marinum is the most frequent non-tuberculous Mycobacterium in humans. We report the first ever described case of epididymoorchitis resulting from hematogenous spread of M. marinum from hand oligoarthritis. This was initially mistaken for rheumatoid disease and methylprednisolone-induced immunosuppression led to hematogenous spread of infection to the testis and epididymis.
Keywords: Mycobacterium marinum; atypické mykobakteriální infekce; výsledek terapie; lidé; Orchitis; Immunosuppressive Agents; Anti-Bacterial Agents; Mycobacterium Infections, Nontuberculous; poranění prstů ruky; Treatment Outcome; Humans; infekční artritida; Middle Aged; epididymitida; Male; Methylprednisolone; Finger Injuries; methylprednisolon; orchitida; lidé středního věku; mužské pohlaví; Epididymitis; antibakteriální látky; imunosupresiva; Arthritis, Infectious; chybná diagnóza; Diagnostic Errors